(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
This article outlines direct (borrowing, calque, literal) and indirect (transposition, modulation, equivalence/reformulation, adaptation, compensation, reduction/expansion) techniques for translating axiological lexemes—value-laden words and expressions—between languages. It argues that successful translation preserves the source text’s “value script” (polarity, intensity, stance) rather than only denotation. Using Uzbek–English examples (e.g., hashar, sumalak, nikah; andisha; kinship terms), the paper shows how connotation, cultural categories, and genre shape technique choice. A brief workflow—sense + value profiling, cultural mapping, technique selection, whole-text validation—supports consistent, reader-appropriate outcomes.